The Understanding the Drivers of Community Choice toward Madrasah Ibtidaiyyah Islamic Centre Bin Baz: Integrating Religious Values and Educational Marketing Approaches: Integrating Religious Values and Educational Marketing Approaches - Ma'ruf, Muammar; Setiawan, Zunan; Adilla, Fitroh (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This qualitative study explores the underlying drivers that influence the community’s decision to enroll their children at Madrasah Ibtidaiyyah Islamic Centre Bin Baz. Anchored in the intersection of religious values and educational marketing, this research seeks to understand how faith-based orientation intertwines with modern educational expectations in shaping parental preferences. Using a phenomenological approach, data were collected through semi-structured interviews, in-depth observations, and document analysis involving parents, teachers, and local community leaders. Findings reveal that religious commitment plays a pivotal role in constructing the community’s perception of educational quality. The school’s emphasis on Qur’anic literacy, moral discipline, and the integration of Islamic identity fosters a sense of spiritual assurance among parents. Beyond this spiritual dimension, educational marketing strategies such as transparent communication, community engagement, and reputation management emerge as complementary factors enhancing trust and loyalty. Parents tend to view the school not only as a center of religious learning but also as a platform that ensures academic competitiveness and social belonging for their children. The study highlights that the community’s choice is neither purely rational nor emotional but a synthesis of both, embedded in cultural, religious, and social contexts. Ultimately, the findings suggest that effective educational marketing within faith-based institutions requires genuine alignment between institutional identity, moral values, and community aspirations. This research contributes to a deeper understanding of how religious values can coexist harmoniously with strategic marketing practices in strengthening parental commitment and sustaining the relevance of Islamic education in a competitive educational landscape.